PCDH10 Interacts With hTERT and Negatively Regulates Telomerase Activity. Issue 50 (December 2015) - Zhou, Li-Na; Hua, Xing; Deng, Wu-Quan; Wu, Qi-Nan; Mei, Hao; Chen, Bing
Abstract : Abstract: Telomerase catalyzes telomeric DNA synthesis, an essential process to maintain the length of telomere for continuous cell proliferation and genomic stability. Telomerase is activated in gametes, stem cells, and most tumor cells, and its activity is tightly controlled by a catalytic human telomerase reverse transcriptase (hTERT) subunit and a collection of associated proteins. In the present work, normal human testis tissue was used for the first time to identify proteins involved in the telomerase regulation under normal physiological conditions. Immunoprecipitation was performed using total protein lysates from the normal testis tissue and the proteins of interest were identified by microfluidic high-performance liquid chromatography and tandem mass spectrometry (HPLC-Chip-MS/MS). The regulatory role of PCDH10 in telomerase activity was confirmed by a telomeric repeat amplification protocol (TRAP) assay, and the biological functions of it were characterized by in vitro proliferation, migration, and invasion assays. A new in vivo hTERT interacting protein, protocadherin 10 (PCDH10), was identified. Overexpression of PCDH10 in pancreatic cancer cells impaired telomere elongation by inhibiting telomerase activity while having no obvious effect on hTERT expression at mRNA and protein levels. As a result of this critical function in telomerase regulation, PCDH10 was found to inhibit cell proliferation, migration, and invasion, suggesting a tumor suppressive role of this protein. Our data suggested that PCDH10 played a critical role in cancer cell growth, by negatively regulating telomerase activity, implicating a potential value in future therapeutic development against cancer.